2013
DOI: 10.1188/13.onf.e358-e367
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Preferences Among Men With Prostate Cancer Receiving Androgen-Deprivation Therapy

Abstract: ADT-induced changes in body composition are believed to contribute to a reduction in insulin sensitivity and dyslipidemia that contribute to increased cardiovascular risk profile. Exercise has the potential to mitigate the harmful effects of ADT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 45 publications
1
51
1
Order By: Relevance
“…The research reviewed here suggests that, in terms of general individual preferences, the following dichotomous alternatives may be a good place to start: (a) supervised or unsupervised, (b) in a group or as an individual, and (c) involving a partner or not involving a partner. These recommendations would be congruent with previous research examining PA preferences in men with prostate cancer …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research reviewed here suggests that, in terms of general individual preferences, the following dichotomous alternatives may be a good place to start: (a) supervised or unsupervised, (b) in a group or as an individual, and (c) involving a partner or not involving a partner. These recommendations would be congruent with previous research examining PA preferences in men with prostate cancer …”
Section: Discussionmentioning
confidence: 99%
“…These recommendations would be congruent with previous research examining PA preferences in men with prostate cancer. 66 Co-ordination of the clinical care team emerged as an integral aspect of initiating and supporting prostate cancer patients with PA behaviour change. If PA roles are assigned sensibly, this may help to accommodate certain barriers to PA promotion that have been reported by healthcare professionals working with cancer patients, e.g.…”
Section: The Potential For a Bidirectional Facilitative Relationshimentioning
confidence: 99%
“…To improve exercise adoption and adherence in prostate cancer survivors, previous studies suggest that programming be individualised (Focht et al, ), tailored to preferences (Harrington, Schwenke, & Epstein, ; Jones & Courneya, ) and be designed with explicit consideration of exercise barriers including comorbidities, fatigue and older age (Craike, Livingston, & Botti, 2011; Keogh, Patel, MacLeod, & Masters, 2014). A systematic review from Wong, McAuley, and Trinh () reported that the majority of cancer survivors were interested in participating in exercise programmes and that tailoring exercise to survivors’ preferences may improve exercise adherence.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review from Wong, McAuley, and Trinh () reported that the majority of cancer survivors were interested in participating in exercise programmes and that tailoring exercise to survivors’ preferences may improve exercise adherence. That said, only two studies have explored both exercise preferences and exercise intentions of men living with prostate cancer (Forbes, Blanchard, Mummery, & Courneya, , ; Harrington et al, ). Harrington et al () found that prostate cancer survivors who had received androgen deprivation therapy (ADT) demonstrated a high level of willingness and acceptability of aerobic and resistance exercise, despite low adherence to aerobic exercise guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence rates for participation in resistance exercise are currently unknown, but the likelihood of prostate cancer survivors' meeting resistance exercise guidelines is low; data involving people without cancer indicate that more than 90% of Australians older than 55 years and 85% of Americans older than 45 years do not participate in sufficient resistance exercise (Humphries, Duncan, & Mummery, 2010;Kruger, Carlson, & Kohl, 2006). In contrast to these high rates of inactivity, the majority of men with prostate cancer who are undergoing ADT express a willingness to participate in exercise programs (Harrington, Schwenke, & Epstein, 2013). These data highlight a gap in supportive care practice and identify a paucity of knowledge regarding effective methods to engage men in long-term exercise participation.…”
mentioning
confidence: 96%